Development of spreadsheet analysis (SAS) for DFA house methodology - Ahmad, Rozie Nani (2004)
Today, the world wide manufacturing companies are increasingly being forced by the market demand to increase the competitiveness of their product in price, quality and delivery time. As a result, the new coherent DFA House Methodology is intended as a design tool to aid the designer in the first step analysis of the system design process. The DFA house Methodology method is minimizing the total number of parts, easy assemblability and improving design quality. This thesis is mainly concerned on the developing the prototype system based on the DFA House Methodology by using the EXCEL prograrmning and VISUAL BASIC as a communication language. This prototype needs to have user fiiendly characteristic interactive, efficient and also runs effectively.